SAT0223 The Onsets of Myositis with Myositis-Specific Autoantibodies (MSAS) are Associated With The Seasons. (23rd January 2014) - Hosono, Y.; Nakashima, R.; Imura, Y.; Yukawa, N.; Yoshifuji, H.; Ohmura, K.; Fujii, T.; Mimori, T.
Abstract : Background: Polymyositis (PM) and dermatomyositis (DM) are systemic connective tissue diseases, and a number of autoantibodies (Abs) are detected in patient sera, some of which are myositis specific. Moreover, MSAs are closely associated with clinical manifestations of PM/DM. Although the cause of myositis is still unclear, several studies have reported the seasonal associations with myositis onset or increased disease activity 1), 2) . However, the previous findings have been different, which may because of ethnicity, sex or environmental factors. Objectives: To assessthe seasonal influence on the onset of the disease in serologically defined subgroups of Japanese PM/DM patients. Methods: Clinical data and serum samples were collected from 121 adult Japanese patients with PM/DM (85 with DM and 36 with PM). Myositis-specific Abs were screened using with RNA immunoprecipitation (anti-synthetases and anti-SRP) and protein immunoprecipitation using [ 35 S] methionine-labelled HeLa cells (anti-p155/140, anti-Mi-2 and anti-MDA5). Results: The profiles of myositis-specific Abs in 121 patients with PM/DM were; 52 (43.0%) with anti-synthetases, 33(27.3%) with anti-MDA5, 15 (12.4%) with anti-SRP positive, 15 (12.4%) with anti-p155/140 positive, and 6 (5%) with anti-Mi-2 Ab. Anti-MDA5, anti-SRP and anti-ARS Ab positive myositis onsets were closely associated with seasons. The onset of anti-MDA5-Ab positive myositis was strongly associated with autumn (Oct-Dec) (N=17, 51.5%, P=0.001). Anti-SRP Ab showed significant seasonal onset in rainy season before summer (Apr-Jun) (N=10, 66.7%, p=0.02). Interestingly, myositis with anti-synthetases Abs developed at seasons except for summer (N=2, 3.8%, p=0.04). Myositis especially DM with anti-synthetases Ab developed less in summer than in other seasons (N=1, 3.2%, p=0.027). The onset of anti-p155/140 and Anti-Mi-2-Ab positive myositis did not show clear association with seasons. Conclusions: The onset of myositis with anti-MDA5, anti-SRP and anti-synthetases Abs were associated with some seasons, anti-SRP with the long spell of rainy season in early summer (Apr-Jun), anti-MDA5 with at autumn (OCt-Dec) and anti-synthetases with the seasons except for summer. Our results provide the consideration of possible relations between other environmental factors which associated with some seasons, such as viral infection or light exposure, and pathogenesis of PM/DM. References: Phillips BA, Zilko PJ, Garlepp MJ, Mastaglia FL. Seasonal occurrence of relapses in inflammatory myopathies: a preliminary study. J Neurol 2002;249:441–4. Leff RL, Burgess SH, Miller FW, Love LA, Targoff IN, Dalakas MC, et al. Distinct seasonal patterns in the onset of adult idiopathic inflammatory myopathy in patients with anti–Jo-1 and anti–signal recognition particle autoantibodies. Arthritis Rheum 1991;34:1391–6. Disclosure of Interest: None Declared